Contabilidad, Medio Ambiente y Educación: Retos frente a los nuevos marcos normativos - Mora García, Yeimer Alexander; Ferrer Manotas, Franklin; Polo, Dany; Villanueva Castro, Mayra Alejandra; Alcantara Galván, Andrea Fernanda; Escobar Merlano, Esmeralda Milena; Peñaranda Roncallo, Sandra Liliana; Ariza Angarita, Yuleida; Hernández Caballero, Francisco (Corporación Universitaria Americana, 2023)
The world changes and with it also the ways of producing, of communicating, of relating commercially, of educating ourselves and of course also the way of approaching environmental care, this book will try to address a series of manifest and determining situations to take into account when making considerations with respect to the environmental issue from the productive apparatus and the academic system. Next, a series of chapters are presented where more than academic reflections, realities from the academy and from the companies with respect to the impact of these in the environment are approached.